Prevalence and Risk Factors of Preterm Premature Rupture of Membranes in Pregnant Women admitted to Hospital, Pakistan - Maryam Shahid, Noor Nishan, Shafaq Saeed Farooqi, Farrah Jabeen, Hina Manzoor, Sohaib Arif, (Pakistan Journal of Medical & Health Sciences, 2022)
In both high- and low-income nations, preterm pre-labou membrane rupture is a significant contributor to perinatal, neonatal, and maternal illness and mortality. Premature membrane rupture puts a woman at risk for postpartum haemorrhage, intraamniotic infection, and even death. The purpose of this study was to ascertain the prevalence of preterm premature rupture of membranes and its related factors among pregnant women admitted to health institutions because little is known about the issue in the study region. A total of 300 participants participated in this research among which 100 had preterm PROM, 100 had PROM, and 100 had preterm deliveries. The ages of the participants ranged from 18-40 years with a mean age of 25.12 ± 4.43 years. Among 300 participants, 9.33, 17.33, 21, 24.33, and 28% were 18-20, 21-25, 26-30, 31-35, and 40 years of age, respectively. Among the total, 19 (6.33%), 271 (90.33%) and 10 (3.33%) were divorced, married and widowed, respectively. Among a total, 44, 40.33, and 15.66% of the participants were multigravida, primigravida, and grand-multigravida, respectively. The majority (87%) of mothers had ANC follow-up in their current pregnancy. In the large population, 255 (85%) had labor pain while 171 (578%) of mothers showed vaginal bleeding in the current pregnancy and 167 (55.67%) of mothers had cephalic presentation. 88.33% of pregnant women had no history of PROM. 97 (32.33%) of mothers had urinary tract infection in pregnancy, 32 (10.66%) had anaemia, and 41 (13.67%) had an abnormal vaginal discharge. The pregnant mothers had not used any cocaine, and cigarettes. Different risk factors associated with PPROM such as current urinary tract infection, gravidity, history of previous PPROM, preeclampsia, economic status, and anaemia were recorded. The major risk factors are use of smoking, chat, and cocaine. To lower the incidence of preterm premature rupture of membranes, early detection and treatment of urinary tract infections and atypical vaginal discharges were advised. Keywords: Preterm prelabour rupture of membranes; fetal outcome; Female urogenital disorders; maternal age; Pakistan